(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2025)
Contemporany Spanish poetry has given convincing signs of its attraction to the Renaissance painter Tiziano Vecellio. The objective of this work is oriented towards the study of references to the work of the Italian artist in the lyrical panorama Spanish modernism. The critical approach to their expressive function in each of them will account for an important series of poetic allusions and ekphrastic or culturalist exercises from a varied range of literary themes and techniques.